Um estudo do significado e sentido da formação continuada de professores para o professor coordenador - Paiva, Luz Heli Maria De [UNIFESP] (2020)
This investigation aims to understand the meaning and the sense of continuous teachers formation for the coordinator teacher and seeks to contribute to the academic debate regarding the improvement of formative processes in the public schooling systems. In order to understand where the formative dimension is inserted in the attributions of pedagogical coordination, a theoretical study was carried which includes a review of the literature and the analysis of the institutional documents which regulate the coordinator function (a) in São Paulo State public schools systems, from its origins to the present days. Of a qualitative character, this study was broadened by field research by means of semi-structured research with the coordinator teachers from different school profiles. The theoretical-methodological approach which underlies this investigation is the Cultural-historical Psychology structured on the studies of Vigotsky (1896-1934), based on the historical-dialectical materialism of Karl Marx (1818-1883) and Friedrich Engels (1820-1895). In order to construct and analyze, the investigation made use of the meaning cores of Aguiar and Ozella (2006, 2013) and Aguiar, Soares e Machado (2015). The understanding of the need to work on teachers continuous formation based on the issues of the school reality comes up a common point in the interviews. What differentiates the three participants is the level of knowledge on how to work on this reality. The relevance of the assistance of the more experience peers springs up as a important mediation the constitution of role of the coordinator. The function of pedagogic coordination in the State of São Paulo is affected by the managerialism in the public schooling which separates those who think out and elaborate the formation from those who execute them in a perspective of dependence and reproduction. In order to overcome this model, it is concluded that, based on this investigation, the State needs to invest resources in its professional collective, among those the supply of consistent and permanent formation with the support and interaction with universities of renowned quality standard in studies development and educational research. The formation process has also to be thought over, in the partnership school and university, so that theoretical and experience knowledge may be converted into new knowledge and that constant investigation be the guideline of the formative processes, having the school as the privileged locus of this formation.